L’aéroport du Bourget et son territoire. Du mythe à la réalité - Antoine Furio (In Situ)
The history of Le Bourget airport is relatively well studied. It is a pioneering site in commercial aviation history and the site of several epic arrivals and departures between the two wars. No research, however, has so far looked at the interactions between the airport platform and the territory where it is located. Obviously, the arrival of the airport and its evolving history had many effects for its environment. The department of cultural heritage of the Seine-Saint-Denis department decided to conduct a study in order to verify this intuition and measure the extent of the airport's impact. Although the communes examined are only the ones within the department, the renewed approach of this research project throws new light on the complex formation of this area of the suburbs to the north-east of Paris. This article, offering a synthesis of the 2015 publication entitled L'Aéroport du Bourget entre les lignes, tries to distinguish between myth and reality in the history of Le Bourget.